The impact of digital currencies on traditional banking systems: An analysis - Ahmad, Syarif (Journal of Economics and Business Letters, 2023)
In the wake of the digital revolution, the financial landscape has seen the emergence of digital currencies as potent tools that promise to redefine traditional banking systems. This paper delves into the myriad ways through which digital currencies influence the operational, regulatory, and competitive arenas of traditional banks. By integrating empirical data analysis with an exhaustive review of current scholarly and industry literature, we uncover the nuanced dynamics between digital currencies and traditional banking institutions. Our investigation reveals that while digital currencies offer unparalleled efficiencies and opportunities for financial innovation, they simultaneously challenge the existing regulatory frameworks and pose risks to the stability and security of traditional financial systems. The outcomes of this research not only shed light on the immediate effects of digital currencies but also pave the way for future inquiries into their long-term implications on the global financial ecosystem.